Florid cystic endosalpingiosis presenting as an ovarian cyst in a postmenopausal woman - Felix Wu Shun Wong; Eric Tat Choi Lee (Wolters Kluwer Medknow Publications, 2016)
This paper presents the case of a postmenopausal woman with a rare florid cystic endosalpingiosis presenting as an ovarian cyst, together with cystic lesions in the pelvis. She had chronic pelvic pain and ultrasound-diagnosed cystic lesions in the pelvis. Surgical laparoscopic management was planned and executed successfully with the condition being diagnosed at the time of surgery and confirmed by histologic analysis. We herein describe the surgical technique used to excise these lesions and present a discussion about the possible implications endosalpingiosis has regarding high-grade serous neoplasms and the tubal origin of these malignancies.